Effect of ageing treatment on the microstructures of ti-50.7at.%ni shape memory alloy - Hastuti, Kurnia (2013)
In this study, a commercial Ti-50.7at.%Ni was subjected to solution treatment at 800°C and 900°C for one hour followed by ageing at 300°C, 400°C, 500°C and 600°C for one hour, two hours and four hours respectively. Characterization of the material using optical microscope, XRD, FESEM and EDX has shown that the presence of Ti2Ni and Ti-rich precipitates in the as-received material remained unchanged even after heat treatment. The presence of oxygen in the air condition heat treatment has stabilized Ti2Ni since this condition causing the formation of Ti4Ni2O which is also determined as Ti2Ni due to their same crystal structure. The formation of Ti3Ni4 precipitates during ageing encouraged the establishment of R phase instead of martensite due to the depletion of Ni content in the matrix. Ageing treatment at 300°C generates two steps of R phase transformation due to the differences in Ni composition in the matrix at the grain boundary and grain interior region. However, for samples subjected to ageing at higher temperature, 400-500°C, only one step of R phase transformation occurred because Ni atomic diffusion was not forbidden in the high temperature. Hardness test performed on the samples revealed that increasing the ageing time will increase the hardness of material; however for the sample aged at 600°C, increasing the ageing time would reduce the hardness due to dissolution of Ti3Ni4 precipitates into the matrix.